The world bank and healthcare reforms a cross‐national analysis of policy prescriptions in South America - Carvalho, Gabriela de (2022)
Recent literature on comparative welfare states has recognised the central role international financial institutions (IFIs) play in shaping social policy. Particularly in low‐ and middle‐income countries (LMICs), where constraints often lead to reliance on foreign resources, IFIs can act as agenda‐setters, transferring their ideas to vulnerable governments. The neoliberal model promoted by IFIs at the end of the 20th century reveals their influence on domestic policy in South America. This study analyses the impact of World Bank (WB) prescriptions on healthcare reform legislation in five South American countries: Argentina, Bolivia, Colombia, Paraguay, and Peru. In doing so, it attempts to answer the following questions: Are LMICs receptive to IFIs’ healthcare system prescriptions? More precisely, have WB policy prescriptions been adopted in healthcare reform legislation in South American countries? If so, in what way? Through content analysis, this study examines domestic healthcare legislation vis‐à‐vis the WB’s prescriptions. The main findings show that countries are receptive to IFIs prescriptions, making them a legitimate source of policy recommendations. Further, the results suggest a correlation between economic development and reliance on foreign resources and the degree to which countries adhere to IFIs prescriptions.
Keywords: South America; World Bank; healthcare legislation; healthcare reform; international financial institutions; low‐ and middle‐income countries; neoliberal health model; Policy transfer; social policy prescriptions